2017
DOI: 10.3389/fonc.2017.00093
|View full text |Cite
|
Sign up to set email alerts
|

The Oncolytic Virotherapy Era in Cancer Management: Prospects of Applying H-1 Parvovirus to Treat Blood and Solid Cancers

Abstract: Non-Hodgkin lymphoma (NHL) and leukemia are among the most common cancers worldwide. While the treatment of NHL/leukemia of B-cell origin has much progressed with the introduction of targeted therapies, few treatment standards have been established for T-NHL/leukemia. As presentation in both B- and T-NHL/leukemia patients is often aggressive and as prognosis for relapsed disease is especially dismal, this cancer entity poses major challenges and requires innovative therapeutic approaches. In clinical trials, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Oncolytic viruses were recently developed for the treatment of blood and solid cancers. 2 They can infect and kill malignant cells while sparing their normal counterparts. 5 So far, there has been no study to report that oVV was applied to treat AML, although oncolytic virus therapy has been used for the treatment of other cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncolytic viruses were recently developed for the treatment of blood and solid cancers. 2 They can infect and kill malignant cells while sparing their normal counterparts. 5 So far, there has been no study to report that oVV was applied to treat AML, although oncolytic virus therapy has been used for the treatment of other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor growth was measured every 3 days and the volume (V, mm 3 was computed using the formula: V=1/2 × length × width) was determined. 2 When the volume of tumors approximately grew up to 200 mm, the mice were injected with PBS, cytarabine, oVV, oVV-ING4 or cytarabine, and oVV-ING4. After 1 week, the tumors of two mice from each group were collected and digested with the help of enzymes into cell suspensions, and then subjected to flow cytometry with Annexin V-FITC/PI double staining.…”
Section: Methodsmentioning
confidence: 99%
“…H-1PV nonstructural protein 1 (NS1) is important for promoting tumor cell death. Preclinical studies suggested that H-1PV can effectively kill various tumor cells [56], including pancreatic ductal adenocarcinoma cells and glioma cells [61]. In particular, ParvOryx (wild-type H-1PV) showed an excellent safety profile in phase I/IIa clinical trials [8].…”
Section: Wild-type Ovs In Oncolytic Virotherapymentioning
confidence: 99%
“…With the FDA’s recent approval of tisagenlecleucel for children and young adults with ALL, it is intriguing to consider whether CAR and OV synergism could be evaluated in haematological malignancy, thus potentially accelerating proof of principle. Certainly, a number of OVs (such as parvovirus and NDV) have been evaluated in preclinical models of leukaemia, lymphoma and myeloma [ 220 , 221 ]. The local induction of innate immunity following OV infection coupled with the potential to enhance CAR T-cell homing and effector function by inserting specific transgenes into the OV genome may be expected to yield improved results with CD19-directed CAR T-cells.…”
Section: Conclusion Outstanding Questions and Potential Future Stramentioning
confidence: 99%